2015
DOI: 10.1177/0741088315576480
|View full text |Cite
|
Sign up to set email alerts
|

Writing, Religious Faith, and Rooted Cosmopolitan Dialogue

Abstract: Some literacy scholars have embraced rooted cosmopolitanism as a framework for educating in today's globalized and pluralistic world, where communicating across difference is an important individual and societal good. But how is the "cosmopolitan turn" in writing complicated by considering the religiosity of writing teachers and student writers? Is it possible for writing instructors and student writers to stay rooted in their own faith traditions, while maintaining openness to other ethical vantage points? Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…He was saying the same thing over and over again. (June 20, 2008) The study's findings confirmed previous studies that illustrated how the inclusion of religious talk in literacy practices creates conflict among youths with different religious orientations (Juzwik & McKenzie, 2015;Reyes, 2009;Skerrett, 2014). The discomfort that the adolescent multilinguals felt in light of engaging with religious identities in literature discussions does not suggest that teachers need to avoid these topics.…”
Section: Dealing With Conflictssupporting
confidence: 77%
See 4 more Smart Citations
“…He was saying the same thing over and over again. (June 20, 2008) The study's findings confirmed previous studies that illustrated how the inclusion of religious talk in literacy practices creates conflict among youths with different religious orientations (Juzwik & McKenzie, 2015;Reyes, 2009;Skerrett, 2014). The discomfort that the adolescent multilinguals felt in light of engaging with religious identities in literature discussions does not suggest that teachers need to avoid these topics.…”
Section: Dealing With Conflictssupporting
confidence: 77%
“…I just tell them that's wrong because it's my responsibility….In my religion, if somebody is doing wrong stuff, you have toyou cannot ignore them" (interview 2). Null's response to religious differences is congruent with how Charlie, in Juzwik and McKenzie's (2015) study, considered convincing nonbelievers about their error as a competition that he had to win. As Juzwik and McKenzie stated, it is difficult to pinpoint what teachers should do to promote religious plurality among students with "deeply rooted resistance to open dialogue across difference" (p. 145) without ascribing "a discourse of moral deficiency" (p. 144) to them.…”
Section: Dealing With Conflictsmentioning
confidence: 59%
See 3 more Smart Citations